Appropriate Technology Innovation “Biopharmaka Grinder” as a Means of Optimizing the Economy of the Senduro Community – Lumajang - Ermawati, Emmy; Istichomah, Istichomah; Urrochman, Maysas Yafi (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2025)
Lumajang Regency, Senduro District, East Java is famous as a center for the production of spices and herbs. Due to its abundant natural potential, various biopharmaceutical plants have been developed and are now major players in the local agricultural industry. The area is rich in natural resources, including vast agricultural lands and a climate that supports the cultivation of many medicinal plants. However, the challenge often faced by farmers is the lack of efficient processing equipment, which hinders the realization of the full potential of these biopharmaceutical components. Appropriate technological innovation The tool known as the “Biopharmaceutical Grinder” is intended to maximize the grinding of several biopharmaceutical raw materials, including spices, herbal plants, and other natural components. Biopharmaceutical Grinder can increase the output and market value of local goods by creating an instrument that is easy to use and friendly to rural communities. The creation and distribution of the Biopharmaceutical Grinder is expected to enhance Senduro's position as a center for biopharmaceutical processing in East Java and make it a model for other regions that want to utilize their natural resources in an environmentally responsible manner.